Identidad comunitaria y el ius puniendi enl a preservación del patrimonio cultural de marcahuamachuco y comandante noel - Pérez Muñoz, Doris Violeta (2014)
In this research, the issue of identity of the Community and the application of the Ius Puniendi, punitive capability inherent in the State addressed, through their legal practitioners, as a means of preserving the cultural heritage. The main objective of the thesis is to demonstrate the need for the consolidation of community identity with their cultural heritage in the towns: Hamlet of Marcahuamachuco, Huamachuco District - La Libertad and the District Commander Noel, Casma Province - Ancash and proper implementation of the Ius Puniendi, to protect and conserve it. The research problem is to determine that the identity of the community and the proper implementation of the Ius Puniendi contribute to the preservation of cultural heritage of localities: Hamlet of Marcahuamachuco, Huamachuco District - La Libertad and the District Commander Noel , Casma Province - Ancash. Likewise, the hypothesis was to determine the identity of the community and the proper application of the Ius Puniendi contributes to the preservation of cultural heritage in these localities. In the theoretical framework we have tried, aside from the general case, items that have to do with the nature of the research topic such as culture, cultural identity, cultural goods and cultural heritage, closely related to both national standards and compared, and a brief analysis of issues such as legal asset and Ius Puniendi in their development and historical, political and legal basis, approach it in the use of methods and techniques as were the Ethnographic which allowed us to learn about the features and cultural reality of the communities under study that is directly related to his identity in the cultural heritage complemented with inductive deductive method that allowed a macro-theoretical pragmatic view of the diversity of identity and awareness of this problem by the study communities, with the support of hermeneutic analysis method also allowed the tax court files and folders; all this with the help of statistics, surveys and interviews that allowed us a qualified view of not only the lack of identity but also of non-suitability of Ius puniendi state.